Automated Audiometry Using Apple iOS‐Based Application Technology. Issue 5 (20th August 2013) - Foulad, Allen; Bui, Peggy; Djalilian, Hamid
Abstract : Objective: The aim of this study is to determine the feasibility of an Apple iOS‐based automated hearing testing application and to compare its accuracy with conventional audiometry. Study Design: Prospective diagnostic study. Setting: Academic medical center. Subjects and Methods: An iOS‐based software application was developed to perform automated pure‐tone hearing testing on the iPhone, iPod touch, and iPad. To assess for device variations and compatibility, preliminary work was performed to compare the standardized sound output (dB) of various Apple device and headset combinations. Forty‐two subjects underwent automated iOS‐based hearing testing in a sound booth, automated iOS‐based hearing testing in a quiet room, and conventional manual audiometry. Results: The maximum difference in sound intensity between various Apple device and headset combinations was 4 dB. On average, 96% (95% confidence interval [CI], 91%‐100%) of the threshold values obtained using the automated test in a sound booth were within 10 dB of the corresponding threshold values obtained using conventional audiometry. When the automated test was performed in a quiet room, 94% (95% CI, 87%‐100%) of the threshold values were within 10 dB of the threshold values obtained using conventional audiometry. Under standardized testing conditions, 90% of the subjects preferred iOS‐based audiometry as opposed to conventional audiometry. Conclusion: Apple iOS‐based devices provide a platform for automated air conduction audiometry without requiring extra equipment and yield hearing test results that approach those of conventional audiometry.